Association of Budd-Chiari syndrome, essential thrombocytosis, and celiac disease - Bakula, Agnieszka; Laguna, Pawel; Cielecka-Kuszyk, Joanna; Kosciesza, Andrzej; Brzewski, Michal; Socha, Piotr (Pediatria Polska - Polish Journal of Paediatrics, 2020)
Herein we report the case of a girl with association of Budd-Chiari syndrome (BCS), essential thrombocythaemia (ET), and celiac disease (CD). To our knowledge, this is one out of eight cases in the literature of BCS complicated with CD, and the only one complicated with ET. This case is particularly significant because anagrelide therapy was started at an unusually early age. A four-year-old girl with ET treated with anagrelide was admitted to our hospital with suspicion of BCS. Ultrasound colour Doppler and computed tomography imaging revealed enlargement of the caudate lobe, splenomegaly, accessory hepatic veins, umbilical vein recanalisation, and ascites. The diagnosis of the CD was confirmed by serology (EmA IgA 1 : 800, tTG IgA > 130 U/ml). Two years later Duhring’s disease was confirmed histologically with recovery after diet modification. Four years later she is still being treated with anagrelide, anticoagulant drugs and is on a well-controlled gluten-free diet.